Empowering MSMEs through Digital Marketing Training for Recipients of Ummul Mukminin Aisyiyah Micro Waqf Bank Capital to Increase Competitiveness in the Digital Market - Aulia Aulia; Firman Syah; Jauhar Mukti (Journal of Universal Community Empowerment Provision, 2025)
As the country with the largest Muslim population in the world, Indonesia has great potential in developing the sharia economy, including strengthening the microfinance sector. Bank Waqf Mikro (BWM) is present as a sharia-based inclusive financial instrument aimed at supporting micro-enterprises around Islamic boarding schools (pesantren). However, low digital literacy and limited access to technology-based marketing remain major challenges for beneficiaries. This community service activity aims to increase the digital capacity of MSMEs assisted by BWM Ummul Mukminin Aisyiyah Makassar through digital marketing training and mentoring programs. Initial results show a 32% increase in participants' understanding of digital marketing concepts based on pre- and post-tests. As many as 85% of participants have successfully uploaded products to social media and marketplaces, although they still require further guidance. In addition, BWM's active involvement as a partner in the recruitment process, moral guidance, and evaluation, significantly contributed to the program's success. Future plans include intensive mentoring through one-on-one coaching, monitoring the program's impact through surveys and sales tracking, and developing a replication blueprint for MSMEs assisted by Aisyiyah in other regions. These findings strengthen the argument that digital training integrated with Sharia-based empowerment can be an effective strategy for increasing the competitiveness of MSMEs. With the support of the right ecosystem, similar programs can become models for sustainable economic empowerment in the era of digital transformation.